Sinergi Tri Pusat Pendidikan dalam Pembentukan Karakter Sosial Peserta Didik - Silmi Afifah; Nur Khasanah (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
Education plays a strategic role in shaping students’ social character, enabling them to adapt and interact positively within society. In modern education, strengthening social character has become essential amid rising individualism and declining empathy among the younger generation. This condition suggests that education still prioritizes cognitive aspects over affective and social dimensions. Collaboration among families, schools, and communities as the Three Centers of Education has not yet functioned optimally, leading to a lack of continuity in social character development. This study aims to analyze the synergy of the Three Centers of Education in shaping students’ social character from an educational sociology perspective. The research employs a descriptive qualitative method through library research, involving a review of books, journals, and relevant previous studies. Data analysis follows the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the synergy among families, schools, and communities significantly contributes to the formation of students’ social character based on moral values, empathy, responsibility, and social awareness. Effective collaboration among these three educational environments fosters a harmonious and sustainable learning atmosphere. The study concludes that the Three Centers of Education function as an interactive social system and serve as an effective strategy to strengthen students’ social character formation in the digital era.